RELETIONSHIP THE LEVEL OF KNOWLEDGE AND ATITUDE WITH THE PRACTICES OF PIG FARMERS AGAINST THE APPLICATION OF BIOSECURITIES IN PAYANGAN DISTRICT, GIANYAR BALI - Suryadhi, Fadhilla; Suada, I Ketut; Wandia, I Nengah (Buletin Veteriner Udayana, 2024)
Farmers play a crucial role in successfully implementation of biosecurity in livestock, this is related to farmers’ knowledge, attitudes, and awareness regarding the importance of biosecurity on their farms. This research aims to assess the level of knowledge, attitudes, and biosecurity practices among farmers, specifically focusing on pig farms in the Payangan District of Gianyar Regency, Bali. Primary data for this study were collected through surveys and directly interviews with 96 breeders. Descriptive analysis was used to discuss the research findings. Additionally, the relationship between independent variables (knowledge and attitudes) and the dependent variable (biosecurity practices) was examined using the Spearman Rank correlation test. In this research, it was found that the level of knowledge of breeders was good, the attitude of breeders was good, and adequate practices regarding the implementation of biosecurity. As for the relationship between levels of knowledge and practice the result was 0.000 (P<0.01), but the r value obtained was very small namely 0.495. Likewise, with the relationship between attitudes and practices, the result was 0.000 (P<0.01), but the r value obtained was very small namely 0.526. In summary, while knowledge and practice are positively related, they represent only a fraction of the factors influencing the successful implementation of biosecurity practices. Based on the result of the study, it can be concluded that pig farms in Payangan District had a good level of knowledge, good attitudes and adequate practices. It is hoped that breeders can maintain their level of knowledge and attitudes, as well as improve biosecurity practices on their farms